An Analysis of the Performance of Micro-entrepreneurs in Twin Cities of Hyderabad - D. , Indira; Y. , Rama Krishna Prasad; K., V.S. Raju; Y. , Jeevan Nagendra Kumar; S. , Ravindrachary; S.V.S.S. , Srinivasa Raju; G. , Rahul Kumar Reddy (International Journal of Psychosocial Rehabilitation, 2020)
Micro-entrepreneurs are small-scale businesspeople who operate with less workforce and low capital. They form a significant part of the informal sector, which makes up 89% of the total workforce in the country (data from the 68th National Sample Survey) and contributes around 38.4% to GDP if agriculture is excluded (Source: Charmes Jacques (2012)) 1. Street vendors are one of the prominent sections of microentrepreneurs who constitute approximately 2 percent of the population of a metropolis and 1 percent of the total country’s population (Sharit K. Bhowmik, 2005). The present study aims to explore the profile of street vendors in terms of their age, gender, experience, education, and marital status. It is an exploratory and descriptive study wherein data was collected from primary and secondary sources. Purposive sampling was used as the number of units in the population is infinite, and a sample size of 1000 was chosen. The study found that most of the street vendors fall within the age group of 40 years. Interestingly, most of them have a basic education. It explored the various types of products sold by street vendors and found that it is a sustainable business in the long run.